Economic post-calculation of the Kaposvári Tömegközlekedési Zrt. for the year 2005 - Veizer, Andrea (Acta Agraria Kaposváriensis, 2006)
I could take part in a trade exercise by the Kaposvári Tömegközlekedési Zrt. with assistance of the Applied Informatical Supply Knowlegde-center and financed by the ROP. During this time my exercise was the systematize and statistical treat of the company’s data, which contained the direct costs depending on the vehicles’ mileage; finally I achieved an economic post-calculation for the year 2005. During the accomplishment of the exercise according to the company’s request I followed with exceptional attention the monthly and yearly development of the repairing hours and costs for all vehicles; at the same time the fueleconomy was not theme of the exercise, although it constitutes a great part of the total costs, because partly it could be a basis of a separate study (because of the complicated normsystem), and partly the company expressly asked preparing of the post-calculation refering the repairing costs (namely for the three activity accomplished by the company: regular bus traffic, separate bus service, and advertising). With this data in the future the management of the company can well-informed decide, for example at the rejuvenation of the vehicles buying the profitable product-types instead of the types with high repairing costs.